Application of a new cavity-loaded factor calibration algorithm on the Test Stand 2 facility at the European Spallation Source - Ma, Jinying; Yang, Lijuan; Qiu, Feng; Wang, Muyuan; Zeng, Rihua; Xu, Chengye; Yu, Jingwei; Maiano, Cecilia; Goudket, Philippe; Lagoguez, Bruno; Pierini, Paolo; He, Yuan (Radiation detection technology and methods, 2024)
Purpose Precise measurements of the cavity-loaded quality factor ( Q L ) are essential for monitoring the performance of superconducting radio frequency cavities. The conventional “field-decay method” cannot be used to measure Q L accurately when the impedance is mismatched. Researchers at the China ADS Front End Demo Linac (CAFe) therefore introduced a new Q L calibration algorithm for mismatched impedance conditions, which they validated through testing at the CAFe facility. The Test Stand 2 (TS2) facility at the European Spallation Source (ESS), which is equipped with a high-power circulator having an adjustable reflection coefficient, provides increased experimental flexibility for validating the proposed CAFe algorithm. The present study further validates the proposed algorithm at the ESS TS2 facility. Methods In this study, we utilized the CAFe algorithm to measure Q L at the ESS TS2 facility in the presence of mismatched impedance. The CAFe algorithm is a modified version of the “field-decay method,” which is based on the cavity differential equation. A more concise alternative derivation of the proposed CAFe algorithm is given in Appendix. The experimental setup at the TS2 facility enables the adjustment of the circulator bias current to vary the reflection coefficient, thereby introducing an impedance mismatch. Our primary focus here is to calibrate the actual values Q L and the cavity detuning Δ f under these mismatch conditions. Results Our results reconfirm the effectiveness of the CAFe algorithm by accurately calibrating Q L and Δ f at the ESS TS2 facility, even when the impedance is mismatched. Our successful calibration of Q L and Δ f under mismatched conditions highlights the practicality and reliability of the CAFe proposed algorithm. When calibrating the cavity half bandwidth and detuning, the Lorentz force detuning and direct current offset may introduce uncertainties of approximately ± 5 Hz and ± 4 Hz, respectively.